Team O2AS at the world robot summit 2018: an approach to robotic kitting and assembly tasks using general purpose grippers and tools. (17th April 2020) - von Drigalski, Felix; Nakashima, Chisato; Shibata, Yoshiya; Konishi, Yoshinori; Triyonoputro, Joshua C.; Nie, Kaidi; Petit, Damien; Ueshiba, Toshio; Takase, Ryuichi; Domae, Yukiyasu; Yoshioka, Taku; Ijiri, Yoshihisa; et al.
ABSTRACT: In this article, we propose a versatile robotic system for kitting and assembly tasks which uses no jigs or commercial tool changers. Instead of specialized end effectors, it uses its two-finger grippers to grasp and hold tools to perform subtasks such as screwing and suctioning. A third gripper is used as a precision picking and centering tool, and uses in-built passive compliance to compensate for small position errors and uncertainty. A novel grasp point detection for bin picking is described for the kitting task, using a single depth map. Using the proposed system we competed in the Assembly Challenge of the Industrial Robotics Category of the World Robot Challenge at the World Robot Summit 2018, obtaining 4th place and the SICE award for lean design and versatile tool use. We show the effectiveness of our approach through experiments performed during the competition. GRAPHICAL ABSTRACT: